2008
DOI: 10.1177/1049909107312594
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Patient Survival by Healthcare Professionals in a Specialist Palliative Care Inpatient Unit: A Prospective Study

Abstract: Accurate prognostication is an enormous challenge for professionals caring for patients with advanced disease. Few studies have compared the prognostic accuracy of different professional groups within a hospice setting. The aim of this study was to compare the ability of 5 professional groups to estimate the survival of patients admitted to a specialist palliative care unit. No group accurately predicted the length of patient survival more than 50% of the time. Nursing and junior medical staff were most accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…18 Dependent mobility represents a simple, practical indicator of reduced functional capacity and in the univariate analyses impacted upon survival time after discharge from a PCU to an RACF. This finding mirrors that of Twomey et al 22 who found independent mobility to be a predictor of length of survival, with nonindependent patients at PCU admission being less than half as likely to survive as long as those able to mobilize on their own.…”
Section: Eastman and Martinsupporting
confidence: 88%
“…18 Dependent mobility represents a simple, practical indicator of reduced functional capacity and in the univariate analyses impacted upon survival time after discharge from a PCU to an RACF. This finding mirrors that of Twomey et al 22 who found independent mobility to be a predictor of length of survival, with nonindependent patients at PCU admission being less than half as likely to survive as long as those able to mobilize on their own.…”
Section: Eastman and Martinsupporting
confidence: 88%
“…However, their precision (calibration) was poor, and their predictions were generally too optimistic. This phenomenon has been previously shown in various other settings [17][19]. However, a well-performed meta-analysis on physician prediction in the ICU setting showed that physician predictions of mortality were more accurate than scoring systems [6].…”
Section: Discussionsupporting
confidence: 63%
“…Of the 42 studies included, 20 reported prognostic estimates using only a categorical approach [19, 20, 2527, 30, 34, 36, 37, 4042, 4547, 49, 55, 56, 58, 60], 16 reported only continuous estimates [21, 22, 24, 28, 29, 31, 33, 38, 39, 44, 48, 5053, 57] and 3 studies reported only probabilistic estimates [32, 43, 59]. Two studies used both categorical and continuous estimates [23, 54] and one study reported all three types of estimates [35].…”
Section: Resultsmentioning
confidence: 99%
“…Two papers could not be included in the forest plot because the relevant data was not available. Twomey, O’Leary, & O’Brien [30] reported that clinicians were just as likely to overestimate as to underestimate survival. Casarett, Farrington, & Craig et al [42] reported the c -statistic for the accuracy of predicting death between one and 10 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation